2022
DOI: 10.3389/fncel.2021.803272
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Combined Nurr1 Overexpression and Natural Inducers on the More Efficient Production of Dopaminergic Neuron-Like Cells From Stem Cells

Abstract: The development of dopaminergic (DA) neurons is a very complex process, and a combination of extrinsic and intrinsic factors involves their differentiation. Transcription factor, Nurr1 plays an essential role in the differentiation and maintenance of midbrain DA neurons. Nurr1-based therapies may restore DA function in Parkinson's disease (PD) by replacing damaged cells with differentiated cells derived from stem cells. Providing tissue-specific microenvironments such as brain extract can effectively induce do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 53 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…Meanwhile, GADD45B is considered as a myeloid differentiation primary response gene ( Abdollahi et al, 1991 ). NR4A2 , also known as nuclear receptor NURR1 , plays a critical role in the differentiation and maintenance of dopaminergic neurons ( Beiki et al, 2021 ). Activator Protein-1 family member JUND is involved in regulating the transcriptional expression of genes related to cell differentiation ( Shaulian et al, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, GADD45B is considered as a myeloid differentiation primary response gene ( Abdollahi et al, 1991 ). NR4A2 , also known as nuclear receptor NURR1 , plays a critical role in the differentiation and maintenance of dopaminergic neurons ( Beiki et al, 2021 ). Activator Protein-1 family member JUND is involved in regulating the transcriptional expression of genes related to cell differentiation ( Shaulian et al, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is possible that the factors expressed by the differentiated P19 cells markedly improve the neurodegenerative effects of toxins in PD models. It has been previously shown that when exposed to various inducers, P19 cells were able to express different factors including nestin, SYP, TH, Onecut (one cut homeobox 1), and neurotrophic factors (NTF) such as BDNF (brain-derived neurotrophic factor), NGF (nerve growth factor), and GDNF (glial cell line-derived neurotrophic factor) [14,15]. Furthermore, these cells can produce and release a highly speci c marker of DA cells, TH, in a differentiated state (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Wistar rat strain was obtained from Isfahan University of Medical Sciences (Isfahan, Iran) and maintained under standard situations (20 ± 2 • C, with a regular dark/light cycle and ad libitum availability in diet and drinking water). First, 28 male rats (220-280 g) were assigned randomly into four groups (Table 1): (1) Sal (control: the rats injected with isotonic saline solution); (2) Par (Parkinson's rat model: 6-OHDA-lesioned animals); (3) Par-E (Parkinson's rats under cell therapy: A line of embryonal carcinoma stem cells, P19 was transfected with pCMV3-GFPSpark vector and injected into the animals); (4) Par-N (Parkinson's rats under cell therapy: P19 ECCs were transfected with pCMV3-C-NR4A2-GFPSpark vector, containing Nurr1 gene, and injected into the animals) [15]. 2.2.…”
Section: Experimental Schemementioning
confidence: 99%
See 2 more Smart Citations